The Impact of Foreign Ownership, Audit Committee, Board of Commissioners, and Audit Specialization on Financial and Environmental Performance: A Comparative Study of Indonesia and Sweden - Pranataningrum, Rr. Arintika (Indonesian Management and Accounting Research, 2022)
This study empirically examines the effects of foreign ownership, audit committees, board of commissioners, and industry specialization on financial performance, with environmental performance as a moderating variable, in Indonesia and Sweden. This study employs quantitative methods with an explanatory research design, utilizing secondary data from annual financial reports spanning 2015-2017. A purposive sampling method was used, resulting in a sample of 57 companies from Indonesia and 50 from Sweden. The findings reveal that foreign ownership positively influences financial performance in Indonesia, while it has no significant effect in Sweden. The audit committee does not positively affect financial performance in Indonesia, but it does in Sweden. The board of commissioners positively impacts financial performance in Indonesia, whereas it does not in Sweden. Industry specialization does not positively influence financial performance in either country. Furthermore, environmental performance does not enhance the positive effects of foreign ownership, the audit committee, the board of commissioners, or industry specialization on financial performance in Indonesia and Sweden.